The influence of a mentally induced mobility restriction on cognitive functioning: An experimental study - Mertens, Alica; Theisen, Maximilian; Funke, Joachim (Open Science Framework, 2020)
This is a registration of a study that aims to examine the influence of a mentally induced mobility restriction on cognitive functioning.
Gesehen am 26.02.2026